The he method diagnostic`s of a station radioreley of communication - Bugera, M. G.; Lutov, V. V.; Rudakov, V. I. (Видавництво Львівської політехніки, 2012)
Diagnostic the station radioreley of communication (RRC) is realizations of modern methods on building control for provides of reliability radioreley station.
Keywords: special function; adaptation; criterion; antenna; receiver; processor